A suitable organic fertilizer substitution ratio could improve maize yield and soil fertility with low pollution risk - He, Hao; Peng, Mengwen; Ru, Sibo; Hou, Zhenan; Li, Junhua (Frontiers in Plant Science, 2022)
Organic fertiliser substitution (OFS) is an effective strategy for reducing the chemical fertiliser usage; however, the effects of different OFS ratios (OFSRs) on maize yield, soil fertility, and heavy metal pollution risk are still unclear. Therefore, determining a suitable OFSR is important. Through the pot experiment, no fertiliser (CK) and organic fertiliser substituting 0% (CF, chemical fertiliser alone), 8% (OF8), 16% (OF16), and 24% (OF24) of the chemical N fertiliser were set to investigate the effects of different OFSRs on maize growth and yield, soil properties (available nutrients, carbon fractions, and carbon pool indices) and nutrients and heavy metals in grain and soil. The results showed that OF8, OF16, and OF24 improved soil fertility by increasing soil organic carbon (SOC, by 10.05%–16.26%) and its fractions, most middle- and micro-nutrients content, and carbon pool management index (CPMI, by 17.45%–30.31%) compared with CF, while improving grain nutritional quality. However, they increased heavy metals content in grain and soil and their Nemerow comprehensive pollution index (NCPI, by 4.06%–16.56% in grain and 2.55%–5.57% in soil) but did not cause pollution. Among them, throughout the growth period, only OF8 treatment increased soil available nitrogen (AN), phosphorus (AP), and potassium (AK) content by 3.04%–11.15%, 7.11%–8.05%, and 0.12%–6.05%, respectively, compared with CF, which thus significantly promoted maize growth and increased yield (by 35.65%); the NCPI of grain and soil was however lower than that OF16 and OF24. In conclusion, substitution ratio of 8% was considered ideal for promoting maize growth, improving yield and soil fertility, with a low pollution risk. The results of this study would aid in guiding the scientific application of OFS technology to agricultural production, thereby contributing to resource utilisation of organic waste and sustainable agricultural development.